Efektivitas Media Edukasi Audio-visual dan Booklet terhadap Pengetahuan Premenopause, Efikasi Diri dan Stres pada Wanita Premenopause di Kota Bandung - Setiawan, Ridwan; Iryanti, Iryanti; Muryati, Muryati (UI Scholars Hub, 2020)
Background. The number of menopausal women in Indonesia is currently 7.4% of the total population, and its number is estimated up to 11.54 % in 2020. The menopausal period is preceded by premenopausal phase in which the estrogen hormone is decreased, causing premenopausal syndromes that may lead to stres in women. Objective. This study was to assses the effectiveness of audio-visuals and booklets as educational medium on the knowledge about premenopause, self-efficacy and stres level of premenopausal women in Bandung. Method. Design of the study was quasi experiment using pre-post test with control group design. There were 76 participants, consisting of 38 participants in intervention group and 38 participants in control group. Results. This study found that the scores of knowledge was higher 6.09 points, self-efficacy was higher 3.05 point, and stres level was decrased by 1.23 point in the intervention group than in the control group. The use of audio-visual and booklet as educational medium was associated with increasing knowledge and self-efficacy as well as effective in reducing stres level in premenopausal women in Bandung City. Conclusion. Providing education through audiovisuals and booklets was effective in increasing knowledge of premenopausal women concerning premenopause.